If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -25 = -8 Reorder the terms: -25 + m = -8 Solving -25 + m = -8 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + m = -8 + 25 Combine like terms: -25 + 25 = 0 0 + m = -8 + 25 m = -8 + 25 Combine like terms: -8 + 25 = 17 m = 17 Simplifying m = 17
| 1.5x+13=2.4+4 | | 8+3z=17 | | log14/x=2 | | 2/3x-5/6x=1 | | (15m2)1/3 | | 45=r-14 | | log8/x=2 | | 5-2k=3 | | 8a+2b-5c+10= | | 6x-16=3x-54 | | n/4=86/344 | | 2p=70 | | X-5+3x-5+4x+10=180 | | -u=61 | | x^2-24=-10x | | 8(x-5)-3=26x-187 | | 21.3+p=30 | | x^2-9y^2-6x-36y-36=0 | | m+10=-78 | | 5(3x-10)=130 | | -24=g+-68 | | m+16=35 | | 2x+3ky+6=0 | | p+-10=-52 | | f-92=7 | | p+0.5=-0.9 | | 4=w+-13 | | f-7=2 | | 3x-5+4x+10+x-5=180 | | br-bs= | | -9=9+v | | 4x=2x+4y |